Cold-seep carbonates of the middle and lower continental slope, northern Gulf of Mexico - Roberts, H H; Feng, D; Joye, S B (Deep-Sea Research. Part II: Topical Studies in Oceanography, 2010)
Authigenic carbonates from cold seeps on the middle and lower continental slope of the northern Gulf of Mexico (GOM) exhibit a wide range of mineralogical and stable isotopic compositions. These carbonates consist of concretions and nodules in surface sediments, hardgrounds of crusts and isolated slabs, and mounded buildups of blocks and slabs of up to over 10 meters in relief above the surrounding seafloor. Mineralogically, the carbonates are dominated by high-Mg calcite (HMC) and aragonite. However, low levels ({<}5 wt{%}) of dolomite are present in most samples. Petrographically, Mg-calcite peloidal matrix and acicular to botryoidal aragonitic void-filling cements are the most frequent associations. The carbon isotopic compositions of the carbonates range from −60.8 to 14.0‰ PDB, indicating complex carbon sources that include 13C-depleted biogenic and thermogenic methane, biodegraded crude oil, seawater CO2, and 13C-enriched residual CO2 from methanogenesis. A similarly large variability in $δ$18O values (2.5 to 6.7‰ PDB) demonstrates the geochemical complexity of the slope, with some samples pointing toward an 18O-enriched oxygen source that is possibly related to advection of 18O-enriched formation water and/or to the decomposition of gas hydrate. A considerable range of mineralogical and isotopic variations in cold-seep carbonate composition was noted even within individual study sites. However, common trends occur across multiple geographic areas. This situation suggests that local controls on fluid and gas flux, types of seep hydrocarbons, the presence or absence of gas hydrate in the near-surface sediment, and chemosynthetic communities, as well as the temporal evolution of the local hydrocarbon reservoir, all may play a part in determining carbonate mineralogy and isotope geochemistry. The carbon isotope data clearly indicate that between-site variation is greater than within-site variation. Seep carbonates formed on the middle and lower continental slope of the GOM do not appear to be substantially different from those found on the upper slope ({<}1000-m water depth). The highly variable fluids and gases that leave their geochemical imprints on seep carbonate of the middle and lower continental slope are similar to their outer shelf and upper slope counterparts.
Keywords: HOV Alvin (Human Occupied Vehicle); ROV Jason (Remotely Operated Vehicle)